A MODEL FOR DEVELOPING HIGH-QUALITY ONLINE COURSES: INTEGRATING A SYSTEMS APPROACH WITH LEARNING THEORY - Maria Puzziferro; Kaye Shelton (Online Learning, 2019)
As the demand for online education continues to increase, institutions are faced with developing process models for efficient, high-quality online course development. This paper describes a systems, team-based, approach that centers on an online instructional design theory (Active Mastery Learning) implemented at Colorado State University-Global Campus. CSU-Global Campus is a newly-created online campus within the Colorado State University System, and launches in Fall 2008 with fully-online undergraduate degree completion programs and Master’s degrees.